Groovy 2 cookbook - Adamovich, Andrey (Packt Publishing, 2013)
This book follows a Cookbook style and is packed with intermediate and advanced level recipes. This book is for Java developers who have an interest in discovering new ways to quickly get the job done using a new language that shares many similarities with Java. The book's recipes start simple, therefore no previous Groovy experience is required to understand the code and the explanations accompanying the examples.